Instructional Supervision by Principals in Type 1C and Type 2 Schools in the Gampaha District Sri Lanka - H. M. Lalitha Kumari (International Journal on Integrated Education, 2022)
This study examined how principals engage in instructional supervision in Type 1C and Type 2 schools in Sri Lanka. Three research questions guided the study to a rational conclusion. Mixed-Method was adopted in the study to triangulate data. Both questionnaire and semi-structured interview schedules were used to collect relevant data from 150 teachers, 8 principals and 8 sectional heads in 8 selected Type 1C and Type 2 schools using the simple random sampling techniques. Tables, percentages and graphs were used to analyze quantitative data and the qualitative data were analyzed using thematic analysis. The findings revealed that all the principals in Type 1C and Type 2 schools in the Gampaha District have positive perceptions about the role of instructional supervision and have formed an instructional supervisory team including the principal. However, the study revealed that the majority of principals in Type 1C and Type 2 schools do not engage in the role of instructional supervision. The study further revealed that the existing internal supervisory team engage in instructional supervision role rarely and do not conduct post observational discussions which facilitate teachers to identify their strength and the areas that need further improvement. It is recommended that, the principals need to carry out adequate instructional supervision of teachers to improve their pedagogical skills and professional development.